Phage display for generating monoclonal antibodies - Frenzel, Andre (Henry Stewart Talks, 2019)
The history of recombinant antibody development, Road to fully human antibodies, Antibody phage display technology, Phage display libraries and generation, Antibody discovery by phage display, Antibody optimization by light chain shuffling, Antibody discovery to difficult targets, Introduction of a full phage display discovery pipeline